Hubungan Kinerja Keuangan Perusahaan dan Nilai Perusahaan - Rezky Yosepha Tarigan; Amrie Firmansyah; Dinis Dwi Shinta Ramadhani; Wishmy Meinawa Ikhsan (Universitas Prasetiya Mulya, 2022)
This study aims to investigate financial performance against value. CEO share ownership is used as a moderating variable in the relationship between the two. The company's performance in this study uses economic value added (EVA). The data used in this study are sourced from the financial statements and stock prices of non-financial companies listed on the Indonesian stock exchange from 2018 to 2020. The data are sourced from www.idx.co.id, the company's official website, and www.finance.yahoo.com. Sampling was conducted by purposive sampling with a total sample that can be used amounted to 84 observations. Research data were tested using multiple linear regression analysis for panel data. This study concludes that the company's financial performance negatively relates to firm value. Meanwhile, the CEO's share ownership did not succeed in having a moderating role in the relationship between firm performance and firm value. Based on the results of this study, the Financial Services Authority needs to increase the role of monitoring the company's performance in aligning the interests of investors.